Accuracy of Sepsis Criteria of ABA versus CDC for CLABSI Diagnosis in Major Burn Patients, and CLABSI Risk Factors - K. Chinaroonchai (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2020. Background: Systemic inflammatory response syndrome (SIRS) can occur as a physiological response without indicating a burn infection. The Centers for Disease Control and Prevention’s (CDC’s) clinical sepsis criteria for infection screening may not be accurate with burn patients, especially for diagnosing central line-associated bloodstream infections (CLABSIs). New clinical sepsis criteria were therefore proposed by the American Burn Association (ABA) in 2007. Nonetheless, no study has compared the accuracy of the ABA and CDC clinical sepsis criteria for burn-CLABSI diagnoses. Objective: The present study aimed to investigate the relative accuracies of the ABA and CDC clinical sepsis criteria for burn-CLABSI diagnoses, and to report the CLABSI incidence at Siriraj Hospital’s Burn Unit. Materials and Methods: A retrospective chart review was conducted of burn patients admitted to the Burn Unit 2007 to 2015. Patients with central venous catheter insertions were included. Details of demographic data; comorbidities; burn type; total burn surface area; and type, duration, and purpose of the central lines were analyzed. The sensitivities and specificities of the ABA and CDC clinical sepsis criteria for CLABSI diagnoses were compared. Results: Of the 101 patients enrolled, CLABSIs were diagnosed in 38 (37.8%). The most common infection site was the internal jugular vein (33%), with CLABSIs occurring most frequently with non-dialysis double lumen catheters. The sensitivity and specificity of the ABA criteria were 76.3% and 93.6%, respectively, with an 85.9% accuracy. Conclusion: The ABA clinical sepsis criteria can be used to diagnose CLABSI in burn patients with acceptable accuracy and a higher specificity than the CDC criteria.